THE DEVELOPMENT OF SCIENCE AND THE FATE OF A SCIENTIST (FOLLOWING GENETICS) - Jonas Rubikas (Problemos, 1997)
In the development of genetics it is possible to see definite levels of investigation. Every level has its characteristic methodology, which includes a set of methods, a subject of investigation, an evaluation, and an interpretation of the results obtained. The beginning of every level is connected with one or a group of scientists whose work and publications produce the beginning of a new level. The beginners and the levels are as follows: 1) G. Mendel, 1865, "The Cell–The Feature"; 2) T. H. Morgan, 1911, "The Chromosome–The Feature"; 3) O. T. Avery et al., 1944, "The DNA Molecule–The Feature"; and 4) V. Gilbert et al., 1975–1977, "The DNA (RNA) Nucleotide Sequence–The Function." One can notice that a change of levels occurs at almost every 30-year period. We are now in the last third of the fourth level of investigation. When the new level appears, the methodological characteristics that will change the present ones will be impossi-ble to foresee. (In reference to the levels of investigation, see Problemos, Nr. 48, p. 56–66, 1995). The development of world-wide science (genetics) could be visualized graphically as a line rising upward through many years and levels. With every new discovery new data are located at the top, which prolong the line. The line of scientific development in a country, in an institute, and in a laboratory, or the line of scientific activity of a scientist will continue at the lower position, as a part of the whole; the distance between these two lines is expressed by the magnitude delta– . The small meaning of delta shows that the work, publication, or scientist is near world-wide science; the large meaning of delta shows the high extent of lagging behind present day world science. The world-wide science line is the background for scientific work evalution: the line goes through levels and at 30-year periods between the levels it goes through the methodological yearly news. If it is important to determine the delta of a work, it is necessary to compare the methodology used in this work with the methodology used according to the world line. The line of scientific activity of a person is under the influence of multiple factors. The line of the scientists at the beginning of activity (doing candidate or contemporary doctoral dissertation work) goes near and parallel to the world-wide science line. After obtaining a particular degree, a declination of the world line appears with the age and absence of renovation of methodology, if the scientist remains in the laboratory as a working person; this is the natural manner of the delta increase. If a scientist begins an administrative career, honorary titles, degrees, posts, and salaries make the declination marked. The line becomes almost horizontal and the delta increases with scientific progress. There are rare exceptions, i.e., a highly positioned scientist with a small delta. At present, the high rate delta scientist whose dissertation was made in a high-rate delta laboratory usually appears after obtaining a habilitated doctorate degree or a simple doctorate. It is very dangerous for scientific development when such a high delta habilitated doctor appears in scientific organizational institutions.